Cytorhizophins A and B, benzophenone-hemiterpene adducts from the endophytic fungus Cytospora rhizophorae. Issue 5 (21st January 2019) - Liu, Hongxin; Tan, Haibo; Wang, Wenxuan; Zhang, Wenge; Chen, Yuchan; Li, Saini; Liu, Zhaoming; Li, Haohua; Zhang, Weimin
Abstract : (±)-Cytorhizophin A and cytorhizophin B (2 ), novel benzophenone-hemiterpene conjugated hetero-dimers featuring an unprecedented 6/7/6/7 tetracyclic fused ring system. Abstract : A pair of novel enantiomeric benzophenone-hemiterpene adducts, (+)-cytorhizophin A (1a ) and (−)-cytorhizophin A (1b ) as well as cytorhizophin B (2 ), all of them featuring an unprecedented 6/7/6/7 tetracyclic fused ring system, together with their biosynthetically related precursor cytorhizophin C (3 ) were isolated from Cytospora rhizophorae A761. Their structures were fully characterized on the basis of extensive spectroscopic analysis, with the absolute configurations of1 determined by X-ray diffraction and electronic circular dichroism (ECD) calculations. Moreover, compounds1–3 were evaluated for in vitro antimicrobial activity.